Bifunctional chimeric fusion proteins engineered for DNA delivery: Optimization of the protein to DNA ratio - Gao, Shan; Simon, Melissa J.; Morrison, Barclay; Banta, Scott (Biochimica et biophysica acta, 2009)
Cell penetrating peptides (CPPs) have been used to deliver nucleotide-based therapeutics to cells, but this approach has produced mixed results. Ionic interactions and covalent bonds between the CPPs and the cargos may inhibit the effectiveness of the CPPs or interfere with the bioactivity of the cargos. We have created a bifunctional chimeric protein that binds DNA using the p50 domain of the NF-κB transcription factor and is functionalized for delivery with the TAT CPP. The green fluorescent protein (GFP) has been incorporated for tracking delivery. The new chimeric protein, p50–GFP–TAT, was compared to p50–GFP, GFP–TAT and GFP as controls for the ability to transduce PC12 cells with and without oligonucleotide cargos. The p50–GFP–TAT construct can deliver 30 bp and 293 bp oligonucleotides to PC12 cells with an optimal ratio of 1.89 protein molecules per base pair of DNA length. This correlation was validated through the delivery of a fluorescent protein transgene encoded in a plasmid to PC12 cells. Thus, self-assembling CPP-based bifunctional fusion proteins can be engineered for the non-viral delivery of nucleotide-based cargos to mammalian cells. This work represents an important step forward in the rational design of protein-based systems for the delivery of macromolecular cargos.